Electronic health records for dummies - Williams, Trenor (--For dummies., 2011)
The straight scoop on choosing and implementing an electronic health records (EHR) system Doctors, nurses, and hospital and clinic administrators are interested in learning the best ways to implement and use an electronic health records system so that they can be shared across different health care settings via a network-connected information system. This helpful, plain-English guide provides need-to-know information on how to choose the right system, assure patients of the security of their records, and implement an EHR in such a way that it causes minimal disruption to the daily demands of a.